Enhancing Adolescent Mental Health Through Independence and Social Support: A Cross-Sectional Study in Makassar, Indonesia - Ibnu, Indra Fajarwati; Sandy, Grestin (Al-Sihah : The Public Health Science Journal, 2025)
Despite the growing recognition of adolescent mental health challenges, there is limited evidence on how adolescent independence and social support interact to influence psychological distress, highlighting the need for contextualized findings to guide mental health interventions. This study explores the relationship between adolescent independence, social support, and psychological distress levels in Makassar, Indonesia. A total of 300 students aged 15–18 years were selected using stratified random sampling. Data collection was performed using validated instruments measuring adolescent independence, social support, and psychological distress levels. Data analysis included descriptive statistics, bivariate analysis (chi-square test), and multivariate analysis (logistic regression) to identify dominant factors influencing adolescent independence. Approximately 60% of adolescents reported high independence, while 75% experienced mild to moderate psychological distress. High social support was significantly associated with greater independence (p < 0.05). Self-efficacy emerged as a key protective factor against psychological distress. These findings underscore the importance of integrating social support and self-efficacy, building programs into school curricula to mitigate anxiety and depression among adolescents.